2017
DOI: 10.1038/ctg.2017.10
|View full text |Cite
|
Sign up to set email alerts
|

Impact of CFTR Modulation on Intestinal pH, Motility, and Clinical Outcomes in Patients With Cystic Fibrosis and the G551D Mutation

Abstract: Objectives:A defect in bicarbonate secretion contributes to the pathophysiology of gastrointestinal complications in patients with cystic fibrosis (CF). We measured gastrointestinal pH, clinical outcomes, and intestinal transit profiles in patients with the G551D mutation before and after treatment with ivacaftor, a CF transmembrane regulator channel (CFTR) potentiator.Methods:Observational studies of ivacaftor effectiveness were conducted in the United States and Canada. A subset of subjects ingested a wirele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
96
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(98 citation statements)
references
References 24 publications
1
96
0
1
Order By: Relevance
“…Increased gastrointestinal acidity has been reported in people with CF due to several factors originating from a dysfunctional CFTR, an ion channel involved in the transport of bicarbonate in pancreatic/biliary ducts, duodenal Brunner glands and others 148,149 . This can lead to inactivation of pancreatic enzymes in the gut and impair fat digestion.…”
Section: Cp-vi Pain Management In Cp Inmentioning
confidence: 99%
“…Increased gastrointestinal acidity has been reported in people with CF due to several factors originating from a dysfunctional CFTR, an ion channel involved in the transport of bicarbonate in pancreatic/biliary ducts, duodenal Brunner glands and others 148,149 . This can lead to inactivation of pancreatic enzymes in the gut and impair fat digestion.…”
Section: Cp-vi Pain Management In Cp Inmentioning
confidence: 99%
“…Secondly, the restoration of CFTR activity could result in a dramatic change in the local pulmonary microenvironment, turning a previously favourable environmental niche into an inhospitable one for resident microbiota. There is evidence to support a similar effect in the GI tract, where CFTR modulation with ivacaftor was associated with improved proximal small intestinal pH, likely secondary to improved bicarbonate secretion [63]. Thirdly, a direct bactericidal effect of ivacaftor itself has been postulated given that its chemical structure contains a quinolone ring and many quinolone derivatives have antimicrobial properties [64].…”
Section: Community Changes Associated With Cftr Modulatorsmentioning
confidence: 99%
“…Gelfond et al have shown that despite changes in pH after short-term CFTR potentiator use, there was no association with symptoms or changes in overall transit time. 92 As motility evaluation in gastroenterology becomes more commonplace, more will undoubtedly be learned about GI transit in CF.…”
Section: Motilitymentioning
confidence: 99%